Designing with Circular Arc Toolpaths to Increase the Complexity of Melt Electrowriting. Issue 10 (3rd May 2022) - Xu, Huaizhong; Liashenko, Ievgenii; Lucchetti, Agnese; Du, Lei; Dong, Yubing; Zhao, Defang; Meng, Jie; Yamane, Hideki; Dalton, Paul D.
Abstract: Melt electrowriting (MEW) is an additive manufacturing technology that fabricates high‐resolution objects. Printing curved and complex patterns, however, requires additional attention and planning to achieve accurate fiber placement. In this context, the jet speed, as measured by the critical translation speed (CTS), is found to be an essential factor for accurately direct‐writing complex nonlinear patterns. When the jet and the translation speed match, the vertical jet better approximates the tool path when the printing is nonlinear. As demonstrated here, the entire printed structure gradually deforms when the jet lag increases. For the first time with MEW, circular arc toolpaths are focused on to expand the design complexity, and there is evidence that the resolution is further improved by printing slightly under the CTS. When using such circular arc toolpaths, inwards tilting of the fiber walls can be observed and can be corrected with microscale layer shifting, shown with scaffolds based on knitting‐type designs. The combination of printing at the CTS with circular arcs increases the manufacturing complexity of curved patterns and has implications for the design and utility of MEW. Abstract : A variety of complex nonlinear scaffolds fabricated by melt electrowriting are reported for the first time. Arcs used as a repeating building block is a simple‐to‐implement but versatile avenue enabling to expand the design freedom of melt electrowriting and 3D print new, complex microstructures tailored for tissue engineering applications.